Suplementasi Minyak Ikan Untuk Peningkatan Imunitas Non Spesifik Udang Vaname (Litopenaeus vannamei) - Vina Olivia Indraswati; Supono Supono; Asep Saefulloh (AQUASAINS, 2015)
Increased immunity shrimp became one of the targets of feeding with a complete nutrient constituent composition. Shrimp have a different immune system compared to fish in general and can be increased quickly by providing the right nutrients. Research nutrient supplementation to increase non-specific immunity, especially in Pacific white shrimp (Litopenaeus vannamei) still rarely done, especially with the addition of fish oil. This research was conducted to study the effect of fish oil supplementation in different oil among lemuru oil and patin oil with a non-specific parameter of Pacific white shrimp among total haemocyte count (THC), the differential haemocyte count (DHC), challenge test with Vibrio harveyi and relative percent survival (RPS). Design of experiments using a completely random design with three treatments and four replications. The treatment is adding  the lemuru oil (treatment A), patin oil (treatent B) and without the addition of fish oil (control). The results showed that the addition of lemuru fish and patin fish oil treatment can increase THC, DHC, which affect the phagocytic activity relative to the level of protection without giving fish oil (P<0.05). The increasing of non-specific immunity of Pacific white shrimp with fish oil needs to analyze in the economic  side to be more economical if applied to the shrimp farmers or commercial feed mills.